Issues and Future Enhancement for Blockchain based E-Voting System - Anubhav Raj Singh, Surendra Kumar, Ravinder Ahuja (International Journal of Advanced Science and Technology, 2020)
Blockchain is the decentralized and immutable mod-ern era technology that is continuously being developed and providing solutions to some of the most important fields of technology. Since its outbreak, the blockchain was famous for its valuable contribution to the transaction field, but after the introduction of smart contracts concept in Ethereum blockchain, the popularity and use of the blockchain have surged. Smart contracts enable us to carry out agreement and transaction trustworthily between two anonymous peers without any central governing authority, because of this feature blockchain can be used to develop a decentralized E-Voting application which can escalate the decreasing level of trust in some of the finest democracies of the world. Replacing the old EVMs with a decentralized blockchain application makes voting an online event. Currently, most of the blockchain-based e-voting systems have issues like scalability and privacy of voters. This paper addresses these issues and provides solutions utilizing Proof of Stake (PoS) based Sharding protocol and zk-SNARKs. This paper highlights how to implement the proposed model and what are the issues that previous models had in the past and their potential solution for a future robust system.Keywords: blockchain, e-voting, ethereum, smart contract, proof of stake, sharding, zk-SNARKs.